ANALISIS KEMAMPUAN MAHASISWA DALAM MELAKUKAN EXPOSÉ ORAL PADA MATA KULIAH FRANÇAIS DU TOURISME - Siti Umaya (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
This study aimed at providing an overview of the ability of eighth semester students in performing exposé oral given that one of the competence of speech that must be achieved by students semester eight competency standard contained in the CECRL document is the competence to conduct exposé. To obtain the necessary data in this study, the author use several research techniques such as direct observation, interviews, questionnaires, library studies, and documentation with the population and sample that is the whole process of exposé oral execution in the course Français du Tourisme and all students semester eight registered follow the course. The authors hope that the results of this study can contribute to improve the quality of teaching especially in the department of French Literature STBA Yapari-ABA Bandung and improvement of speaking ability of eighth semester students by using French in accordance with the competence standards set in CECRL.